Dr Non-oil taxation and government expenditure in Nigeria: feedback from co-integration analysis (Journal of Economic Research & Business Administration, 2021)
Sequel to the paucity of government revenue to fulfill fiscal responsibilities because of downplayedoil revenue from world market, Nigeria government invariably veered to nonoil taxation as a pertinentsource of revenue to actualize government expenditure. Therefore, this study appraised nonoil taxationeffect on government expenditure from 1981 to 2019 in Nigeria. This study further assessed the bearingof causality amid Government Expenditure, Value Added Tax, Company Income Tax, Custom andExcise Duties and Education Tax, enthusiastically hiring VECM, Johansen co-integration, Units root, andGranger causality tests. Outcomes bared that Value Added Tax has positive significant effect on GovernmentExpenditure. Furthermore, Value Added Tax granger- cause government Expenditure, also governmentExpenditure granger- cause Value Added Tax. It is also exposed that Company Income Tax hadlong run and short run positive significant outcome on government Expenditure. More so, Custom andExcise Duties and Education Tax upsurges government Expenditure positively and significantly. Conclusively,nonoil taxation enhanced government expenditure positively, strongly and significantly. Thisrevealed that economic benefits that accrued from nonoil taxation income have effectively expended ongovernment expenditure in terms of fulfilling both the current and capital expenditure as expected. It isadvocated that government should expedite more nonoil taxes collection devices to avail more incomewhich can be empathically, judiciously, effectively and prudently expended on government expenditurefor more anticipated civil responsibilities from the populace.Key words: Value Added Tax, Custom and Excise Duties, Education Tax, Company Income Tax,Government Expenditure.